(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
This research was purposes to develop a program of ethical leadership enhancement of school administrators under the Office of Basic Education Commission. It was the researcher for development by applying the components and developed indicators of ethical leadership enhancement of school administrators to develop into manual for the use of the program of ethical leadership enhancement of school administrators in 9 aspects, and 8 activity sets. Moreover, there was the evaluation through analysis of the needs of leadership and interview with experts by evaluating with a group of teachers and personnel representatives, school administrators and directors of the educational service area offices. The findings were as following: The program of ethical leadership enhancement of school administrators under the Office of Basic Education Commission features 6 elements which are 1) Principle; 2) Purpose; 3) Goal; 4) Duration; 5) Content of 8 Activity Sets (namely: Activity 1 Loyalty; Activity 2 Organizational Commitment; Activity 3 Justice; Activity 4 Integrity; Activity 5 Thinking Reflection; Activity 6 Credibility; Activity 7 Vision; and Activity 8 Responsibility); 6) Development Process and Enhancement Methods with 4 steps; 7) Innovation Media or Learning Resources; 8) Pre and Post Evaluation for monitoring after the development and satisfaction assessment; and 9) Achievement Condition which the evaluation was at a high and the highest level in all aspects. The experts have assured that the utility is appropriate at a high level.